DEVELOPMENT OF WEBSITE-BASED LEARNING MEDIA ON MEDIA ELEMENTS AND TELECOMMUNICATION NETWORKS AT SMK NEGERI 1 PAINAN - Ferju Prihamdani; Thomson Mary; Rini Novita (Kresnamedia Publisher, 2026)
This study aims to develop a website-based learning media for the Basic Computer and Telecommunication Network Engineering subject, particularly the Media and Telecommunication Networks topic for Grade X TJKT students at SMK Negeri 1 Painan. The research was motivated by limited practical facilities and the lack of interactive learning media, which resulted in low student learning outcomes. This study employed the SDLC iterative model consisting of requirements analysis, design, development, testing, and implementation. Data were collected through expert validation sheets and practicality questionnaires for teachers and students. The developed media integrates visual materials, instructional videos, and interactive quizzes to support independent learning. Validation results indicate that the media achieved a software quality evaluation score of 88.19%, while practicality scores reached 95.48% from teachers and 86.75% from students, categorized as highly practical. These findings demonstrate that the proposed web-based learning media is feasible and effective in supporting the teaching and learning process in vocational education, particularly in improving students’ understanding of abstract networking concepts